2012
DOI: 10.1371/journal.pone.0049872
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in a Northern Canadian First Nation Population: Dietary Intake, Serum Concentrations and Functional Gene Polymorphisms

Abstract: The wide spectrum of vitamin D activity has focused attention on its potential role in the elevated burden of disease in a northern Canadian First Nations (Dené) cohort. Vitamin D insufficiency, and gene polymorphisms in the vitamin D receptor (VDR) and vitamin D binding protein (VDBP) have been implicated in susceptibility to infectious and chronic diseases. The objectives of this study were to determine the contribution of vitamin D from food, and measure the serum concentrations of 25-hydroxyvitamin D3 (25-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
5
40
0
Order By: Relevance
“…The longer form exhibits 1.7x less efficiency than the shorter form (33). Furthermore, high frequency of the VDR (ATG) (f) allele was associated with a decrease in Th1 immune response (17). A previous study on the role of the FokI SNP demonstrated the presence of increased vitamin D levels in carriers of the TT (ff) genotype, as compared with carriers of the CC (FF) genotype (34).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The longer form exhibits 1.7x less efficiency than the shorter form (33). Furthermore, high frequency of the VDR (ATG) (f) allele was associated with a decrease in Th1 immune response (17). A previous study on the role of the FokI SNP demonstrated the presence of increased vitamin D levels in carriers of the TT (ff) genotype, as compared with carriers of the CC (FF) genotype (34).…”
Section: Discussionmentioning
confidence: 95%
“…A previous study demonstrated that GC single nucleotide polymorphisms (SNP) may affect blood plasma vitamin D levels (17). The VDR gene also exists in certain genetic variants, which may modulate the biological effect of vitamin D in target cells (18).…”
Section: Introductionmentioning
confidence: 99%
“…To date, certain polymorphisms situated in GC have been reported to be associated with vitamin D metabolite levels in blood plasma (13,52). The GC rs7041 SNP was associated with high concentrations of VDBP in blood plasma and a high binding affinity to 25(OH)D 3 in a Canadian cohort (13).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Luo et al (49) demonstrated that the BsmI SNP was responsible for the significantly lowered VDR mRNA levels in patients bearing the A (B) allele as compared to bearers of the GG (bb) genotype. The FokI polymorphism results in the creation of two protein variants; longer VDR, encoded by the changed allele form (ATG) (f), has an additional three amino acids and is 1.7 times less efficient than the shorter, common allele form (ACG) (F) (50 (13) demonstrated high frequency of VDR f allele associated with a downregulation of the Th1 immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation